Intense deposition and rapid processing of seafloor phytodetritus in a glaciomarine fjord, Andvord Bay (Antarctica). (August 2020) - Ziegler, A.F.; Cape, M.; Lundesgaard, Ø.; Smith, C.R.
Highlights: Phytodetritus can be quantified using oblique time-lapse seafloor imagery. Rapid deposition of phytodetritus forms a food bank that feeds benthos in winter. Deposition of phytodetritus is related to sea-ice cover but not to surface winds. Amythas membranifera processes the surface 1 cm of sediment annually. Abstract: The West Antarctic Peninsula (WAP) region encompasses numerous fjords known to be hotspots of benthic biodiversity and biomass. These ecosystems are undergoing rapid climate warming and oceanographic change; consequent glacial melt and retreat may dramatically alter benthic communities and ecosystem functions in WAP fjords. In addition, there is extreme variability in seasonal productivity and phytodetrital food input to the deep shelf benthos of the WAP. Here we document the flux and utilization of phytodetritus at 530 m depth in Andvord Bay, a WAP glaciomarine fjord, using seafloor time-lapse images spanning a 10-month period, from December 2015 to September 2016. To explore the relationship between sea-surface conditions and detrital export, we developed a color-based method to quantify seafloor phytodetritus cover in time-lapse images, and correlated phytodetritus cover with sea-ice cover and surface wind speed. During the most rapid period of phytodetritus accumulation in early January 2016, approximately 3 cm of phytodetritus was deposited on the fjord floor over six days, representing a large input of organic carbon to the benthos. The timing of this rapid export event was not related to overlying wind conditions and occurred when the fjord was ice-free. To assess the response of the megafaunal community, we measured fecal-pellet production by the dominant surface deposit-feeder, the ampharetid polychaete Amythas membranifera . The deposit-feeding rate of A. membranifera increased substantially during high seafloor phytodetritus cover and returned to background levels for the rest of the autumn and winter. Ampharetids and mobile megafauna were observed to feed throughout the entire time-series, including beneath winter sea ice, suggesting that the delivery of phytodetritus from surface phytoplankton blooms in spring/summer sustains these abundant populations year-round with a sediment food bank. A. membranifera can reach densities of >37 m −2 and, as a population, processes a volume equivalent to the top 1.05 cm of sediment annually. The maximum individual feeding rates measured are comparable to some temperate intertidal deposit feeders. Nonetheless, phytodetritus on 31–73% of the seafloor was consumed by macrofauna or microbial populations not visible in time-lapse photographs, suggesting that recently deposited phytodetritus is processed primarily by these smaller size classes. This study demonstrates the seasonal coupling and subsequent decoupling of detritivore activity in response to a massive detrital deposition event in a deep, subpolar WAP fjord. This work indicates that both megafaunal deposit feeders and smaller size classes play important roles in processing labile organic matter in WAP fjord ecosystems.